Task complexity, age and gender effect on functional motor asymmetry of right- and left-handed children - Paula Cristina Rodrigues; Sara Cristiana Moreira Carneiro; Isabel Cabral; Maria Olga Vasconcelos; João Manuel Barreiros (Desafio Singular, 2011)
Manual asymmetry was assessed in different complexity coincidence-anticipation tasks in 59 right- and 56 left-handed children of both genders divided into two age groups (7-8 years and 9-10 years). Results revealed that (i) manual asymmetry increased with task complexity in both handedness groups without reaching statistical significance for the left-handed group; (ii) for the left-handed group, manual asymmetry was evident in all measured errors; (iii) better performance was presented when executing simpler tasks for both handedness groups; (iv) maturational effect was more pronounced in the complex task; (v) in both handedness groups, the 9-10-year-old group was more accurate and less variable when compared to the 7-8 year-old group; (vi) interaction between age and task complexity revealed that males outperformed females in both handedness. These results favor the perspective in which handedness is seen as a dynamic process, where motor preference interacts with task complexity.